2014
DOI: 10.3892/ijo.2014.2531
|View full text |Cite|
|
Sign up to set email alerts
|

USP22 promotes the G1/S phase transition by upregulating FoxM1 expression via β-catenin nuclear localization and is associated with poor prognosis in stage II pancreatic ductal adenocarcinoma

Abstract: Ubiquitin-specific protease 22 (USP22), a newly discovered member of ubiquitin hydrolase family, exhibits a critical function in cell cycle progression and tumorigenesis. The forkhead box M1 (FoxM1) transcription factor plays a crucial role in cell proliferation, differentiation and transformation. However, the expression and functions of USP22 in pancreatic ductal adenocarcinoma (PDA) and whether FoxM1 is involved in USP22-mediated cell cycle regulation have not been studied. We examined the expression of USP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…As early as 2005, USP22 was identified as a member of an 11-gene "deathfrom-cancer" signature for highly aggressive tumors (15). Elevated expression of USP22 has since been reported to be a prognostic factor for poor survival in patients with colorectal cancer (16), breast cancer (22), pancreatic cancer (26,27), cervical cancer (28), oral squamous cell carcinoma (29), hepatocellular carcinoma (30), and gastric carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2005, USP22 was identified as a member of an 11-gene "deathfrom-cancer" signature for highly aggressive tumors (15). Elevated expression of USP22 has since been reported to be a prognostic factor for poor survival in patients with colorectal cancer (16), breast cancer (22), pancreatic cancer (26,27), cervical cancer (28), oral squamous cell carcinoma (29), hepatocellular carcinoma (30), and gastric carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…Because USP22 is functionally correlated with Wnt/β-catenin signaling regulators and proteins Foxm1 and GSKβ [7, 16], we hypothesized that USP22 maintains CRC cell stemness and tumorigenesis through Wnt/β-catenin signaling. To explore this hypothesis, we performed RT-PCR and western blot assays for Wnt/β-catenin signaling target genes (Axin2, MYC and Cyclin D1) in USP22 knockdown Caco2 and HCT15 stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to promote cell cycle progression and tumorigenesis [7-9]. Furthermore, USP22 expression correlates with CRC progression and therapy failure [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that, during the embryonic period, FOXM1 is overexpressed in all tissues (15); however, in adulthood, FOXM1 expression only occurs in the tissues with active proliferation and metabolism (16). In various types of tumor cells, FOXM1 is highly expressed in the nucleus and cytoplasm, and causes the dysfunction of regulation processes (17)(18)(19)(20)(21). In particular, FOXM1 controls mitotic entry by the periodic upregulation of a group of genes that are maximally expressed as cells progress through the late G2 and into the M phase (14).…”
Section: Introductionmentioning
confidence: 99%